2021
DOI: 10.1097/ico.0000000000002722
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Densitometry Assessed With Scheimpflug Camera in Healthy Corneas and Correlation With Specular Microscopy Values and Age

Abstract: Purpose: To investigate correlations between specular microscopy endothelial parameters and age with corneal densitometry values, as they are presented from a Scheimpflug device, in different levels of the cornea.Methods: Two hundred eighty-four eyes of 142 healthy subjects were included in this observational, prospective study. Corneal densitometry was evaluated with Scheimpflug imaging system in the central 0-to 2-mm annular zone of the cornea, whereas the endothelial cell properties were assessed with the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
2
4
0
1
Order By: Relevance
“…Our perioperative data showed that the anterior layer had the highest densitometric values, followed by the stroma and the lowest endothelium. Similar tendencies were proven in the literature using a Pentacam, [12,13,17,18] confocal microscope [19,20], and scatterometer, [21] making our measured values more reliable.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our perioperative data showed that the anterior layer had the highest densitometric values, followed by the stroma and the lowest endothelium. Similar tendencies were proven in the literature using a Pentacam, [12,13,17,18] confocal microscope [19,20], and scatterometer, [21] making our measured values more reliable.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we focused on assessing densitometry in the central 0–2 mm zone, as we examined the corneal endothelium in the central 0.25 mm*0.55 mm range. Recently, CD has been regarded as an objective and noninvasive tool to monitor corneal endothelial health [ 16 , 18 ]. Tekin and Karmiris found a correlation between CD and age and first investigated the correlation between densitometry and endothelial morphometry in healthy corneas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously found that densitometry does not appear to correlate with either keratometry or refractive power [22]. Although an increase in corneal densitometry has been found in healthy eyes with age [32], the age analysis of the N and KC groups showed that the average densitometry was weakly correlated with age among the N group, but moderately correlated with age among the KC group. This may be linked to the severity of KC being more likely to be higher with age, as it is a progressive condition [13].…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown an increase in corneal densitometry with age in normal participants with the changes being attributed to the changes in endothelium with aging. 15,16 This study only included children with healthy corneas in the normal group; hence, no changes in corneal densitometry are expected to be found with age in this cohort.…”
Section: Discussionmentioning
confidence: 99%